Assessment of Students’ Satisfaction with Sports and Recreational Services in Southwestern Nigeria Federal Universities - Comfort A. Okotoni; Ayotunde S. Akinwale; S. ‘Tayo Subair (IJORER : International Journal of Recent Educational Research, 2024)
Objectives: This study assessed the level of adequacy of sports and recreational services in federal universities in Southwestern Nigeria. It also determined the level of students’ satisfaction with sports and recreational services in the study area. The study equally examined the influence of sports and recreational services on students’ satisfaction in the study area. Method: This study employed descriptive survey research design using quantitative approach. The population for the study comprised 193, 526 students from the seven federal universities in Southwestern Nigeria. The sample for the study was 1,144 students from three selected universities in the region. One instrument was used for the study, namely; Students’ Satisfaction with Sports and Recreational Services Questionnaire (SSSRSQ). Data were analysed using percentages and weighted average. Results: The results revealed that sports and recreational services in the study area were moderately available with weighted average of (2.6). The result also showed that students were moderately satisfied with sports and recreational services with average mean of 52%. It was further revealed that sports and recreational service (β=0.168; p<0.05) had significant influence on students’ satisfaction in the study area. Novelty: This research presents novelty research that combines the variables of sports and recreational services and students’ satisfaction. The research is intriguing due to variation in emphasis, research participants, results of the study and the implication for students’ personnel administration in tertiary institutions.